(untitled) (Plant Bulletin, 2025)
Argan tree (Argania spinosa) is a medium-sized, multipurpose, thorny tree of calcareous semi-arid regions. Initial attempts were made to introduce it into the arid regions of Pakistan. Effects of different seed sowing techniques and soil types on plant growth parameters were evaluated throughout the year. Seed sowing techniques were compared based on their impact on germination (%), germination period (days), plant growth (cm), plant height at 45 and 90 days after germination (DAG), number of leaves at 45 and 90 DAG, root length at 45 and 90 DAG and survival rate with different combinations of soil types (sandy, loamy, organic matter, farm yard manure, coconut peat, sand: peat and sand: organic matter (1:1). Results revealed that seed cracking and soaking for 96 hours and improved germination rates (59.2 and 38.6%), reduced germination periods (14 and 26 days), better overall plant growth compared and enhanced survival rate of 75.16 and 60.18%, respectively as compared to un-soaked and un-cracked seeds. Coconut peat showed the most favorable conditions for seedling establishment and early growth with highest germination (71.65%), survival rate (85.62%), lowest germination period (10 days) and the lowest seed deterioration (28.64%) among all treatments. Coconut peat had the highest plant growth rate per day of 0.36 cm/day, followed by sandy soil (0.23 cm/day) and the lowest growth rate exhibited by loamy soil of 0.10 cm/day during the suitable environmental conditions. Seed germination and plant growth are strong negative correlation with the higher temperatures (>30°C) and lower humidity.